Swine-Derived Probiotic Lactobacillus plantarum Inhibits Growth and Adhesion of Enterotoxigenic Escherichia coli and Mediates Host Defense - Wang, Jing; Zeng, Yanxia; Wang, Sixin; Liu, Hui; Zhang, Dongyan; Zhang, Wei; Wang, Yamin; Ji, Haifeng (Frontiers in Microbiology, 2018)
Weaning stress renders piglets susceptible to pathogen infection, which leads to post-weaning diarrhea, a severe condition characterized by heavy diarrhea and mortality in piglets. Enterotoxigenic Escherichia coli (ETEC) is one of typical strains associated with post-weaning diarrhea. Thus, prevention and inhibition of ETEC infection are of great concern. Probiotics possess anti-pathogenic activity and can counteract ETEC infection; however, their underlying mechanisms and modes of action have not yet been clarified. In the present study, the direct and indirect protective effects of Lactobacillus plantarum ZLP001 against ETEC infection were investigated by different methods. We found that bacterial culture and culture supernatant of L. plantarum ZLP001 prevented ETEC growth by the Oxford cup method, and ETEC growth inhibition was observed in a coculture assay as well. This effect was suggested to be caused mainly by antimicrobial metabolites produced by L. plantarum ZLP001. In addition, adhesion capacity of L. plantarum ZLP001 to IPEC-J2 cells were observed using microscopy and counting. L. plantarum ZLP001 also exhibited a concentration-dependent ability to inhibit ETEC adhesion to IPEC-J2 cells, which mainly occurred via exclusion and competition mode. Furthermore, quantitative real time polymerase chain reaction (qPCR) analysis showed that L. plantarum ZLP001 upregulated the expression of host defense peptides (HDPs) but did not trigger an inflammatory response. In addition, L. plantarum ZLP001 induced HDP secretion, which enhanced the potential antimicrobial activity of IPEC-J2 cell-culture supernatant after incubation with L. plantarum ZLP001. Our findings demonstrate that L. plantarum ZLP001, an intestinal Lactobacillus species associated with piglet health, possesses anti-ETEC activity. L. plantarum ZLP001 might prevent ETEC growth, inhibit ETEC adhesion to the intestinal mucosa, and activate the innate immune response to secret antimicrobial peptides. L. plantarum ZLP001 is worth investigation as a potential probiotics.